Paradoxical effect of SARS‐CoV‐2 infection in patients with immune thrombocytopenia. (10th September 2020) - de la Cruz‐Benito, Beatriz; Rivas‐Pollmar, María I.; Álvarez Román, María T.; Trelles‐Martínez, Roberto; Martín‐Salces, Monica; Lázaro‐del Campo, Paula; Ramírez‐López, Andrés; García‐Barcenilla, Sara; Cebanu, Tamara; Acuña‐Butta, Paula; Monzón‐Manzano, Elena; González‐Zorrilla, Elena; et al.
Summary: Thrombocytopenia has been identified as a common complication of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection in the general population. In an attempt to determine the impact of coronavirus disease 2019 (COVID‐19) in patients with immune thrombocytopenia (ITP), a retrospective single‐centre study was performed. Thrombocytosis was observed in patients with chronic ITP after SARS‐CoV‐2 infection, frequently needing treatment adjustment or even discontinuation of therapy. Relapses and newly diagnosed cases showed a fast response after initial treatment compared to ITP. Reduced immune activity due to lymphopenia during COVID‐19 could explain this paradoxical effect, although further studies are needed.